Development of Web-Based Digital Mathematics Modules Grade VII SMPN 1 Watansoppeng - Sri Rahmawati; Nurhikmah H; Awaluddin Muin (Inovasi Kurikulum, 2024)
The development of digital mathematics modules in the digital era offers vital relevance in enhancing learning effectiveness. This research applies the research and development (R and D) approach to the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. This research aims to holistically identify needs, design, and evaluate the digital modules. The trial respondents are 29 seventh-grade students from SMP Negeri 1 Watansoppeng. The modules are validated by subject matter and media experts. Additionally, based on trial results, the modules are deemed practical due to positive responses from students. Analysis of learning test results shows a significant improvement in post-test scores, and N-gain analysis indicates the effectiveness of the modules in enhancing student understanding. This research concluded that the digital modules are effective and suitable for use in the context of mathematics learning in schools. The digital modules as an alternative have significant potential to enhance the quality of mathematics education, particularly in leveraging digital technology as an effective and relevant learning tool. Using web-based digital mathematics modules developed through the RD approach with the ADDIE model represents a progressive step in supporting teaching and learning mathematics in the current digital era. AbstrakPengembangan modul digital matematika di era digital menawarkan relevansi yang vital dalam meningkatkan efektivitas pembelajaran. Penelitian ini menerapkan pendekatan research and development (R and D) dengan model ADDIE, yang mencakup lima tahapan, yaitu analisis, desain, pengembangan, implementasi, dan evaluasi. Tujuan penelitian ini adalah untuk mengidentifikasi kebutuhan, merancang, dan mengevaluasi modul digital tersebut secara holistik. Responden uji coba is 29 peserta didik kelas VII SMP Negeri 1 Watansoppeng, modul ini dinilai valid oleh validator ahli materi dan media. Selain itu, dari hasil uji coba, modul ini dianggap praktis berdasarkan respon positif dari peserta didik. Analisis tes hasil belajar menunjukkan peningkatan yang signifikan pada nilai posttest, dan hasil analisis N-gain menunjukkan efektivitas modul dalam meningkatkan pemahaman siswa. Dari hasil penelitian ini, disimpulkan bahwa modul digital tersebut efektif dan layak digunakan dalam konteks pembelajaran matematika di sekolah. Modul digital sebagai sebuah alternatif yang memiliki potensi besar untuk meningkatkan kualitas pembelajaran matematika, khususnya dalam memanfaatkan teknologi digital sebagai sarana pembelajaran yang efektif dan relevan. Penggunaan modul digital matematika berbasis web yang dikembangkan melalui pendekatan R and D dengan model ADDIE merupakan langkah progresif dalam mendukung pengajaran dan pembelajaran matematika di era digital saat ini.Kata Kunci: Basis website; modul digital; Matematika; website